2019
DOI: 10.1103/physrevmaterials.3.075201
|View full text |Cite
|
Sign up to set email alerts
|

Transport of hot carriers in plasmonic nanostructures

Abstract: Plasmonic hot carrier devices extract excited carriers from metal nanostructures before equilibration, and have the potential to surpass semiconductor light absorbers. However their efficiencies have so far remained well below theoretical limits, which necessitates quantitative prediction of carrier transport and energy loss in plasmonic structures to identify and overcome bottlenecks in carrier harvesting. Here, we present a theoretical and computational framework, Non-Equilibrium Scattering in Space and Ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…18 ). It indicates that the hot holes with higher energy could only be collected within a shorter distance, agreeing with the reported simulation result due to the shorter mean free path of hotter carriers 9 , 11 . At −0.6 V, the energy barrier is only about 0.1 eV lower than the excitation laser energy (1.96 eV).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…18 ). It indicates that the hot holes with higher energy could only be collected within a shorter distance, agreeing with the reported simulation result due to the shorter mean free path of hotter carriers 9 , 11 . At −0.6 V, the energy barrier is only about 0.1 eV lower than the excitation laser energy (1.96 eV).…”
Section: Resultssupporting
confidence: 91%
“…After generation in the nanoscale localized and strongly enhanced plasmonic electric field, the hot carriers can only travel a few tens of nanometers before they lose their energy by thermalization via the electron–electron scattering and electron–phonon scattering, which has been revealed by the theoretical calculation 9 , 10 . The consequent spatial distribution of the hot carriers may determine the active area on the surface, which is crucial to efficiently capture the hot carriers for achieving highly efficient SP-based catalysts or optoelectronic devices 5 , 9 , 11 . Recently, the spatial distribution of hot carriers has been visualized via ex situ scanning electron microscope or florescence imaging of the reaction or stained products of the hot carriers-induced reaction 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…33,42,43 Jermyn et al for example, have recently reported the results of models for the energetic and spatial distributions of hot electrons in Au nanorods that are in excellent agreement with HSQ exposures observed in this work. 43 In this work, we coarsely estimate the energy of hot electrons generated in the nanoantennas by calculating resistive losses and assuming that on the timescale of the laser pulse all power dissipated by resistive loss is carried 6 by conduction electrons in Au. Based on these assumptions and approximations, we hypothesize that hot electrons 1.5 eV above the Fermi level of Au may have sufficient energy to initiate the dissociation of water, which subsequently drives hydrolysis and crosslinking of HSQ.…”
supporting
confidence: 86%
“…The recent report by Jermyn et al shows that the distribution of hot carriers is expected to peak at the center of nanorod antennas. 43 These hot electrons may carry sufficient energy to dissociate species on the Au surface via mechanisms such as dissociative electron attachment. 59,60 Dissociation of water due to hot electrons could play an important role in the crosslinking of HSQ, as water dissociation products would support the hydrolysis of silane groups in HSQ.…”
Section: Figures 2a and 2bmentioning
confidence: 99%
“…The reduced dimensions of the heteronanostructures minimize the probability of undergoing another relaxation/recombination process [68]. While the injection of hot electrons (using n-type semiconductors such as TiO 2 ) is the most accepted plasmon-driven charge transfer mechanism, there exist recent interesting studies claiming the importance of hot holes in other plasmonic-based systems [73,86,92,97,134,135,136,137] such as Au-NiO x , Au-pGaN [73], Au nanorods coated with a CoO nanoshell [138], Au nanostructures [101,139,140], or Ag-BiOCl hybrids [86,137].…”
Section: Discussionmentioning
confidence: 99%